Protocol of quantitative ultrasound techniques for noninvasive assessing of hepatic steatosis after bariatric surgery - Chen, Bin; Lu, Qijie; Hu, Bing; Sun, Di; Ying, Tao (Frontiers in Surgery, 2024)
the efficacy of QUS techniques assessing hepatic steatosis compared to other methods before and after bariatric surgery.Prior to the fomal study, we recruited 21 obese Chinese participants who received ultrasonic examination (TAI, TSI) and MRI-PDFF. AC-TAI showed moderate correlations with MRI-PDFF (adjusted r=0.632; P<0.05). For MRI-PDFF ≥10%,SC-TSI showed moderate correlations with MRI-PDFF (adjusted r=0.677; P<0.05)Our pre-experiment results signified that using QUS techniques for postoperative evaluation of bariatric surgery is promising. QUS techniques will be signed a widespread availability, real-time functionality, and low-cost approach for assessing hepatic steatosis before and after bariatric surgery in obese individuals, thus is capable for subsequent scale-up liver fat quantification.The present research endeavor has been bestowed with the imprimatur of the Ethics Committee of the Hospital, as indicated by its Approval Number: 2023-KY-015. In due course, upon completion of the study, we intend to disseminate our findings by publishing them in a suitable academic journal, thereby facilitating their widespread utilization.